Recommendations for the Development of a New operational classification System For The Foodservice Industry. (August 2013) - Barrows, Clayton; Vieira, Edward T.
The foodservice industry is large and diverse, demanding an adequate system for classifying its many different types of operations. There are many different classification systems in use by industry and researchers. Although many of the current systems offer certain benefits, some do not provide the necessary framework for researchers and some do not provide realistic groupings for purposes of industry benchmarking. Furthermore, in many cases, classification systems are not compatible with one another. This article reviews some of the systems that are currently in use and argues for the need for a single common classification system. Finally, it proposes a new system, based on certain operational factors, which can be used by both industry and academics in the effort to provide consistency across academia and industry.